Wymiar i cele polityki regionalnej w zintegrowanej Europie - wybrane aspekty - Rynio, Dorota (Dimension and Goals of Regional Policy in Integrated European - Selected Aspects, 2005)
High level of differentiation of development of regions in the countries of European Union is a reason for the increase of meaning of regional policy. Common regional policy implies support for retarded regions, ultra-peripheral, with structural problems regions. It also serves a general development of human resources and hardens activities in the European strategy of employment. Because of the EU enlargement some regions cannot get help in Target 1; the reason is that average GNP per capita has increased - the regions can receive help in Target 2 and 3. The character of regional policy of EU changes in influence of world economy and globalization process. Enlarged EU can compete with the economy of the USA. The new area of EU is a diversified and full of discrepancies region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 212-226